Визначення пазового розсіювання статора асинхронного двигуна з урахуванням насичення, зігзаг-розсіювання, взаємної індуктивності фаз - Попович, О.М.; Головань, І.В. (Електротехніка і електромеханіка, 2011)
Possibility of an allowance for zigzag dispersion and mutual inductance of phases along the slot dispersion paths when determining slot dispersion in an asynchronous motor stator is shown. Studies with formation of dependences of slot dispersion inductance change versus rotor rotation angle change and versus current magnitude at a ratio to the rated value are carried out.